Proposta de ferramenta digital para o auxílio ao planejamento de processo de soldagem - Roos, Luis Alberto (2020)
This academic work refers to development of a digital tool of planning and controlling of welding processes on welded sets. The system generate a planning’s sequence with the project's initial data input, establishing the necessity of human technique and resources, predicting planning possibilities through internal research based in past experiences and similar products, verifying tools and equipment involved, the need for human qualification, supporting technical documents and others that could be incorporated into platform odules as needed by the user. In this sense is shaped the platform’s concept to be implemented according to the metalworking industry' need that nowadays could have deficiencies in developing welding processes due to a lack of a patterned system of planning and controlling that could be conducted by a technician from the sequences' organization of presented by the software, and with this, raising the degree of technical assertiveness and optimize costs involved, besides keeping a traceability able to sustain the homologation of products to its customers. Using development’s software Visual Studio 2015, were developed registration modules of data that posterior are selected from system menus, complementing technical information needed to the planning of welding process and, by the end, are compiled in a way of a standard planning, following to the factory environment and shop floor and engineering sectors to final homologation.